2015
DOI: 10.1063/1.4935845
|View full text |Cite
|
Sign up to set email alerts
|

Landau damping of Langmuir twisted waves with kappa distributed electrons

Abstract: The kinetic theory of Landau damping of Langmuir twisted modes is investigated in the presence of orbital angular momentum of the helical (twisted) electric field in plasmas with kappa distributed electrons. The perturbed distribution function and helical electric field are considered to be decomposed by Laguerre-Gaussian mode function defined in cylindrical geometry. The Vlasov-Poisson equation is obtained and solved analytically to obtain the weak damping rates of the Langmuir twisted waves in a nonthermal p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 36 publications
2
13
0
Order By: Relevance
“…The study of plasma dynamics with finite OAM has predicted new effects and nontrivial properties attributed to finite OAM in plasmas. The examples are twisted waves and associated instabilities [ Mendonca et al , ; Mendonca , ; Shukla , ; Khan et al , ; Arshad et al , , ].…”
Section: Introductionmentioning
confidence: 99%
“…The study of plasma dynamics with finite OAM has predicted new effects and nontrivial properties attributed to finite OAM in plasmas. The examples are twisted waves and associated instabilities [ Mendonca et al , ; Mendonca , ; Shukla , ; Khan et al , ; Arshad et al , , ].…”
Section: Introductionmentioning
confidence: 99%
“…The resultant equation is then multiplied by F pl and integrated in rdr with orthogonality condition described in Ref. 34. After applying the orthogonality condition, the final form of resultant equation is given as…”
Section: Plasma Dispersion Function With Helical Electric Fieldmentioning
confidence: 99%
“…By definition of Laguerre-Gaussian (LG) function F pl ðr; zÞ (which is described in Ref. 34 with its properties as well), the potential /ðr; tÞ can be written as follows:…”
Section: Plasma Dispersion Function With Helical Electric Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…They have shown that the DIA waves can support solitary structures associated with both positive and negative potential due to the presence of non-thermal electrons in their dusty plasma model. However, a lot of theoretical observations of space plasmas [19,20,21,22,23,24,25,26] are often characterized by a particle distribution function with high energy tail and they may deviate from the Maxwellian distribution. Superthermal particles may arise due to the effect of external forces acting on the natural space environment plasmas or to wave particle interaction.…”
Section: Introductionmentioning
confidence: 99%